Association between triclocarban and triclosan exposures and the risks of type 2 diabetes mellitus and impaired glucose tolerance in the National Health and Nutrition Examination Survey (NHANES 2013–2014). (March 2020) - Xie, Xin; Lu, Congying; Wu, Min; Liang, Jiayu; Ying, Yuting; Liu, Kailiang; Huang, Xiuxia; Zheng, Shaoling; Du, Xiuben; Liu, Dandan; Wen, Zihao; Hao, Guang; et al.
Highlights: Women are more likely to be exposed to triclocarban and triclosan than men. Triclocarban exposure is positively associated with the risk of T2DM in women but not men in the USA. Triclosan exposure is not associated with the risk of T2DM in the USA. Abstract: Background: There has been increasing interest in the concept that exposure to environmental chemicals may be contributing factors to epidemics of diabetes mellitus (DM). Triclocarban and triclosan (TCs) are synthetic antibacterial chemicals that are widely used in personal care products. Studies have shown that TCs are endocrine disruptors that alter metabolic conditions. However, it remains unclear whether exposure to TCs is a risk factor for impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM). Objective: We explored the hypothesis that TCs exposure is associated with an increased risk of IGT and T2DM. Method: To test our hypothesis, we analyzed the U.S. National Health and Nutrition Examination Survey (NHANES) cross-sectional data from 2013 to 2014. IGT and T2DM were diagnosed based on an oral glucose tolerance test (OGTT) and the WHO standards. The levels of urinary TCs were measured using an HPLC-MS/MS method that NHANES investigators developed. The association between urinary TCs status and IGT and T2DM was examined separately in men and women using multivariable logistic regression models adjusted for age, race, BMI, education, ratio of family income to poverty, smoking, exercise and hypertension. Results: Nine hundred US participants (429 men and 471 women) were included in the analysis, of whom 242 (26.89%) were diagnosed with T2DM and 117 (13.00%) had IGT. Among women, there was a significant positive association between triclocarban, but not triclosan exposure and T2DM (OR: 1.79, 95% CI: 1.05, 2.05) after adjusting for potential confounding factors. Among men, no significant association between TCs exposure and IGT or T2DM was observed. Conclusions: Triclocarban exposure may increase the risk of T2DM in the women, although additional studies are needed to confirm the results of this study and to investigate the underlying mechanisms.